Densità di energia di deformazione locale e resistenza a fatica di giunti saldati di geometria complessa - M. Zappalorto; F. Berto; P. Lazzarin (Fracture and Structural Integrity)
A recent criterion based on the local strain energy density (SED) averaged over a given control volume is applied to well-documented experimental data taken from the literature, all related to steel welded joints of complex geometry. This small size volume embraces the weld root or the weld toe, both regions being modelled as sharp (zero notch radius) V-notches with different opening angles. The SED is evaluated from three-dimensional finite element models by using a circular sector with a radius equal to 0.28 mm. The data expressed in terms of the local energy fall in a scatter band recently reported in the literature, based on about 650 experimental data related to fillet welded joints made of structural steel with failures occurring at the weld toe or at the weld root.